Entre o sol e a liberdade impera a violência: formação de redes para a ação a partir da estratégia saúde da família - Oliveira, Kalyane Kelly Duarte de (2011)
The research aimed to analyze the feasibility of forming a network of municipal services to prevent and treat child victims of violence from the Basic Health Units in the Family Mossoró / RN. The research is a qualitative approach and was developed in the form of action research. The population was composed of representatives of institutions of the child and primary care professionals. Data were collected through questionnaires, workshops and semi-structured interview. The results were analyzed from data collected through the questionnaire designed to assess the material, lectures, dialogues and assessments with the team and presented in accordance with the findings of the research. The study was approved by the Ethics in Research UFRN with protocol No. 158/2010, CAAE: 0176.0.051.000-10. Situational diagnosis in the participants answered a questionnaire to characterize and then launched the guiding question of the focus group FHS While professional what your perception towards violence against children? It was felt the fear and ignorance on the part of the unit staff on how to prevent and to refer cases of violence against children and adolescents in the area of coverage of the unit and also realized that the professionals felt victims of occupational violence before the violence has reached proportions that the area of the unit. Mind the need to change strategies to work to combat violence, we plan to conduct focus group workshop to complete the questionnaire, training for protection against occupational violence, and meeting with other bodies responsible visor protecting children and adolescents to draw the flowchart of the victims in safety net. The next moment training to fill the notification form professionals were interested in learning and use this tool to combat violence. At the third meeting in Unity, meeting with representatives of the Child Protection Council, the professional unit showed interest in interacting with the agency to expose and combat violence against children and adolescents. Due to difficulties in the physical structure of the unit was not possible to continue the research and planned every moment, and then completed the data collection with interviews with the participating professionals, to assess the meetings. Therefore, it is considered that action research has also achieved its goals because the team was involved in the collective construction of a proposed change in the practices of referral and prevention of violence against children and adolescents. This involvement was favored using the principles Freirian during the course of the study. However, it is assumed that the network was not fully implemented because it is known that it is in a continual process of improvement and must continue evolving with the unit team.